2018
DOI: 10.3389/fnhum.2018.00446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Definition Transcranial Direct Current Stimulation of the Right Inferior Frontal Gyrus on Empathy in Healthy Individuals

Abstract: Empathy, including cognitive and emotional empathy, refers to the ability to infer the mental states of others and to the capacity to share emotions. The neural mechanisms involved in empathy are complex and not yet fully understood, and previous studies have shown that both cognitive and emotional empathy are closely associated with the inferior frontal gyrus (IFG). In this study, we examined whether empathy can be modulated by high-definition transcranial direct current stimulation (HD-tDCS) of the right IFG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…The rIFG may be involved in emotion recognition (through emotional‐communicative information, such as facial expressions) and conversion of the observed facial expressions of pain into a pattern of neural activity that would enable the observer to infer the state of the expresser, thus providing the neural basis for emotional empathy. In line with these observations, non‐pain facial expression‐based empathy necessitates the activity of the rIFG, as revealed by a recent cortical stimulation study (Wu et al, 2018). However, a few studies have also found that, when participants focused on pain using objective cues about the sensory component of the observed pain (e.g., pain in limbs), the rIFG also demonstrated stronger activation (Grèzes, Armony, Rowe, & Passingham, 2003; Iacoboni, 2005; Iacoboni, 2009; Vachon‐Presseau et al, 2012).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The rIFG may be involved in emotion recognition (through emotional‐communicative information, such as facial expressions) and conversion of the observed facial expressions of pain into a pattern of neural activity that would enable the observer to infer the state of the expresser, thus providing the neural basis for emotional empathy. In line with these observations, non‐pain facial expression‐based empathy necessitates the activity of the rIFG, as revealed by a recent cortical stimulation study (Wu et al, 2018). However, a few studies have also found that, when participants focused on pain using objective cues about the sensory component of the observed pain (e.g., pain in limbs), the rIFG also demonstrated stronger activation (Grèzes, Armony, Rowe, & Passingham, 2003; Iacoboni, 2005; Iacoboni, 2009; Vachon‐Presseau et al, 2012).…”
Section: Introductionsupporting
confidence: 57%
“…However, Massey et al found that decreased cortical thickness of the rIFG was associated with worse performance in cognitive empathy tasks among individuals with schizophrenia (Massey et al, 2017). In line with these observations, cognitive empathy necessitates the activity of the rIFG, as revealed by a recent tDCS brain stimulation study, and this tDCS effect is also negatively correlated with scores on the FS subscale (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moral judgment of food-wasting and harmful scenarios also revealed an increased activation in several unique areas (absent in morally disgusting and dishonest conditions) including the bilateral Supplementary Motor Area, as well as the Inferior Frontal Gyrus, Putamen and the Amygdala in the left hemisphere. These regions correspond with the neural network involved in empathy (Del Casale et al, 2017; Goerlich-Dobre, Lamm, Pripfl, Habel, & Votinov, 2015; Wu et al, 2018). However, we did not observe activation of the so-called pain matrix (anterior Insula, anterior Cingulate Cortex), which in previous studies consistently showed increased activation while experiencing pain oneself, as well as while watching others experience pain (Lamm, Decety, & Singer, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…First, participants' trait cognitive empathy and trait emotional empathy were measured using the IRI, which has four subscales: the perspective-taking and fantasy subscales represent cognitive empathy, while the empathic concern and personal distress subscales represent emotional empathy [ 28 , 29 ]. Second, as the MET has higher ecological validity for assessing cognitive empathy and emotional empathy than self-reported questionnaires [ 30 ], the Chinese version of this task (MET-C) was also used. It involves 40 pictures of people in various emotional states (20 positive and 20 negative emotional valence pictures).…”
Section: Methodsmentioning
confidence: 99%